Effects of Different Chloride Salts and Fat Levels on the Quality Characteristics of Beef Patties - Baris Yalinkilic (International Journal of Gastronomy Research, 2024)
The aim of this study was to investigate the effects of different chloride salts (four formulation with NaCl, KCl, CaCl₂, and MgCl₂) at 2% w/w level on the pH, color, sensory, and cooking properties of beef patties formulated with two levels of tail fat (10% and 20%). The results indicated that the use of CaCl₂ and/or MgCl₂ resulted in a significant (P < 0.01) decrease in the pH values of both uncooked and cooked beef patties. The salt factor significantly influenced the a* value of uncooked beef patties (P < 0.05). It also affected the a* (P < 0.01) and b* (P < 0.01) values of cooked beef patties.. The highest L* value (P < 0.05) in uncooked beef patties was observed with 20% fat usage. Use of CaCl₂ and/or MgCl₂ in the salt formulation significantly affected the cooking yield, moisture retention (P < 0.01), patty diameter, and shrinkage parameters (P < 0.05). On the other hand, the fat factor significantly influenced all cooking properties at the P < 0.01 level, except for the decrease in thickness.  Except for salinity and bitterness, the salt factor significantly influenced the sensory scores of the samples. The use of CaCl₂ and/or MgCl₂ in the salt mixture for beef patties resulted in lower sensory scores for the product's sensory parameters. In conclusions, KCl was found to produce satisfactory results as a substitute for NaCl. In contrast, it was concluded that CaCl₂ and/or MgCl₂ salts were not suitable substitutes for NaCl.